Determinants of gold price trend using econometric modeling / Ahmad Haziq Azmi, Noor Syamimi Muhamad Azlan and Nursyafarah Amalina Roslan - Azmi, Ahmad Haziq; Muhamad Azlan, Noor Syamimi; Roslan, Nursyafarah Amalina (2017)
This study involves in discovering the gold price trend and the factors that influence the gold price. Moreover this study also help the investors to know the gold price whether it will fall or rise in the certain time. The study used the Simple Linear Regression to screening the interaction between the dependent variable and the independent variable. The data is a time series data as it was taken monthly from January 2012 until December 2016. The results were found there are significant interaction between the gold price and the independent variable which are silver price, inflation rate (Consumer Price Index), exchange rate, interest rate, gross domestic products (GDP) and Brent crude oil. Then, the final result of the econometric modeling were obtain and the model very precious for the investors and both academic.